Analisis Peran Promosi Kesehatan Dalam Mendukung Keberhasilan Program Pencegahan Penyakit Tidak Menular Di Indonesia - Keren Stelin Maliangkay; Ummi Rahma; Safanny Putri; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Non-Communicable Diseases (NCD) are chronic and non-communicable diseases that cannot be transmitted from one person to another in any form. Currently PTM is a serious global health problem, which is marked by the emergence of new cases and deaths from Non-Communicable Diseases (NCD) every year. Prevention and management of PTM must be done as early as possible considering that PTM sufferers have a low quality of life, causing the burden of health costs to increase thereby increasing the mortality rate. One effective strategy to prevent an increase in the number of PTM sufferers is to carry out health promotion programs. Health promotion is carried out to empower individuals and communities to consciously involve themselves in adopting healthy living habits. This study uses the Systematic Literature Review (SLR) method. Data collection was carried out by analyzing various reading sources or literature relevant to the research topic. A literature search was carried out using the Google Scholar electronic site in the form of a search engine with the keywords health promotion, prevention programs and Non-Communicable Diseases (PTM). There are 6 articles related to the role of health promotion in supporting the success of non-communicable disease prevention programs. Based on the analysis conducted, it can be concluded that the role of health promotion is needed to support the success of non-communicable disease prevention programs in Indonesia. Because one of the effective strategies to prevent the increasing number of PTM sufferers is to carry out health promotion programs.